The Relationship Between Physical Activity and Physical Fitness of Elementary School Students Aged 10–12 Years - Ilmul Ma'arif; Puguh Satya Hasmara (Universitas Majalengka, 2023)
All forms of physical activity or daily human movement activities always require physical support and fitness, so that there are problemsthat occur when physical abilities or fitness is not in good condition will be something to note because physique and fitness are the basic factors for any human activity. This study aims to determine the relationship between physical activity and physical fitness of students aged 10-12 years in Sekolah Dasar Negeri Bakalan Kecamatan Gondang Kabupaten Mojokerto. This type of research is a type of correlational research that aims to find the presence or absence of a relationship, the results of the study show that the value of physical fitness and physical activity obtained is in the moderate category, while for the correlation test obtained significant = 0.038 with a degree of significance p = 0.05. Based on the calculation results, it shows that there is a significant relationship between physical activity and students' physical fitness, with a proven significance value of 0.038 < 0.05. The conclusion ofthe h asil is that between physical activity and physical fitness affect each other or there can be a relationship.